Analisis Kekasaran Permukaan Pemotongan Sisi Gerak Melingkar pada CNC Milling - Andika, Wendy Putra; Husman, Husman; Yunus, Muhammad (Jurnal Inovasi Teknologi Terapan, 2024)
Minimal Surface Roughness results are the desired goal in the CNC Milling machining process for circular motion side cutting with the right machining process parameters in order to obtain minimal workpiece Surface Roughness response results. This study was conducted in order to obtain parameters that contribute greatly to surface roughness and determine the effect of parameter variations on the LAGUN MC 750 CNC milling machine using the Taguchi research method. The machining process parameters varied were spindle speed (2,400 RPM, 3000 RPM), depth of feed (0.2 mm, 0.4 mm) and feeding movement (clockwise, counterclockwise) using S45C steel material. The results of this study show that minimal roughness results are obtained with a spindle speed of 2400 RPM, a depth of feed of 0.2 mm, and a counterclockwise feeding movement.